Association of left atrium voltage amplitude and distribution with the risk of atrial fibrillation recurrence and evolution after pulmonary vein isolation: An ultrahigh‐density mapping study. (27th May 2019) - Ballesteros, Gabriel; Ravassa, Susana; Bragard, Jean; Ramos, Pablo; López, Begoña; Vives, Enrique; Neglia, Renzo; Wise, Bernardo; González, Arantxa; Moreno, María U.; Díez, Javier; García‐Bolao, Ignacio
Abstract: Introduction: Ultrahigh‐density‐voltage mapping (uHDV M) is a new tool that can add new insights into the pathophysiology of atrial fibrillation (AF). The aim of this study was to evaluate the performance of uHDV M in predicting postablation AF recurrence (AFR). Methods and Results: We included 98 consecutive patients undergoing pulmonary vein isolation for AF (40.8% persistent) using an uHDV M system and followed for 1 year. The left atrium (LA) mean voltage ( V m ) and the V slope (slope of the voltage histogram calculated by linear interpolation, with the relative frequency on the vertical axis and the bipolar potential on the horizontal axis) were calculated from 12 567 ± 5486 points per map. Patients with AFR (N = 29) had lower V m and higher V slope as compared with patients without AFR (N = 69). Receiver operating characteristic curves identified V m as the strongest predictor of AFR, with a higher incidence of AFR in patients with V m 0.758 mV (57.6%) or lower than patients with V m higher than 0.758 mV (15.4%; P  < .0001). Among patients with V m  higher than 0.758 mV, patients with V slope 0.637 or higher exhibited higher ( P  = .043) AFR incidence (31.3%) than patients with V slope lower than 0.637 (10.2%). This classification showed incremental predictive value over relevant covariables. V m values were lower and V slope values were higher in patients that progressed from paroxysmal to persistent AF. Patients with Vslope 0.637 or higher had a 14.2% incidence of postablation atypical atrial flutter, whereas patients with V slope lower than 0.637 did not present this outcome. Conclusions: The risk of AFR, atrial flutter, and progression from paroxysmal to persistent AF can be detected by quantitative analysis of LA uHDV M identifying diverse patterns of atrial substrate alterations.